TEMPERATURE DEPENDENCES OF ELECTRIC RESISTANCE IN CARBON COMPOSITE MATERIALS IRRADIATED BY ELECTRONS AT DIFFERENT DOSE RATE - Aimuratov, D.B.; Kupchishin А.I. (Recent Contributions to Physics, 2008)
The radition-initiated structural changes observable in carbon polymer composites to lead to non-standard dose and temperature dependences of electric resistance.